A Proof-of-Concept Study Evaluating the Phosphodiesterase 10A Inhibitor PF-02545920 in the Adjunctive Treatment of Suboptimally Controlled Symptoms of Schizophrenia. Issue 4 (July 2019) - DeMartinis, Nicholas; Lopez, Rene N.; Pickering, Eve H.; Schmidt, Christopher J.; Gertsik, Lev; Walling, David P.; Ogden, Adam
Abstract: Background: Effective treatments for managing suboptimal clinical responses to current therapy for schizophrenia remain a critical unmet need. Phosphodiesterase 10A (PDE10A) inhibition represents a mechanistically novel approach to the treatment of schizophrenia, with preclinical studies suggesting improvements in partially responsive symptoms could be achieved via adjunctive use of the PDE10A inhibitor PF-02545920. Therefore, the adjunctive safety, tolerability, pharmacokinetics, and efficacy of multiple repeat doses of PF-02545920 were investigated in a phase 1b study and subsequent phase 2 study. Methods: The phase 1b study randomized 37 adult patients with stable symptomatology and stable antipsychotic regimens within 3 cohorts. Study participants received ascending doses of PF-02545920 or placebo for 10 to 18 days. The phase 2 study randomized 240 outpatients with stable symptomatology but suboptimal response to current antipsychotic regimens 1:1:1 to PF-02545920 5 mg, PF-02545920 15 mg, or placebo every 12 hours for 12 weeks. The primary efficacy end point of the phase 2 study was change in the Positive and Negative Syndrome Scale total score from baseline to week 12, with changes in other clinical assessments as secondary end points. Results: Treatment was well tolerated, and observed PF-02545920 exposures were within the range predicted to be adequate for demonstrating efficacy. However, no significant differences in the prespecified efficacy end points between the 2 PF-02545920 treatment arms and placebo were observed. Conclusions: Current data and results of a prior monotherapy study in which PF-02545920 failed to differentiate from placebo refute the hypothesis that PDE10A inhibitors have use as antipsychotic agents for schizophrenia. Abstract : Supplemental digital content is available in the text.